DESIGN AND EVALUATION OF MOSQUE SYSTEM USING RAD AND CSI - Effendi, Diana; Dhaniawaty, Rani Puspita; Hidayat, Rahmat; Alghani, Muhammad (Universitas Royal, 2025)
Abstract: Mosques are places of jamaah and centers of social and economic activity for Muslims. Still, in the process of managing their activities, DKM administrators often face challenges related to efficiency, integration, and transparency of information. This research aims to develop a web-based Mosque Management Information System (SIMMAS) that integrates the management of ZISWAF (zakat, infaq, sadaqah, waqf), qurban, inventory, activity information, and digital payments via QRIS. Using the Rapid Application Development (RAD) method, the system was designed to be developed quickly and in alignment with user needs. The evaluation was conducted using the Customer Satisfaction Index (CSI) approach, involving 60 respondents comprising mosque administrators and congregants. The results show that all SIMMAS services received CSI scores above 85%, indicating a high level of user satisfaction, particularly with the religious lecture scheduling feature. Nevertheless, there remains room for improvement, especially in the responsiveness and empathy aspects of financial and inventory services. This research is expected to serve as a foundation for the continued development of SIMMAS to become more effective, efficient, and digitally integrated in mosque management. Keywords: user satisfaction; mosque information system; CSI; SIMMAS; ZISWAF Abstrak: Masjid merupakan tempat ibadah, pusat aktivitas sosial dan ekonomi umat Islam, namun dalam proses pengelolaan kegiatannya, pengurus dkm kerap menghadapi tantangan terkait efisiensi, integrasi, dan transparansi informasi Penelitian ini bertujuan untuk mengembangkan Sistem Informasi Manajemen Masjid (SIMMAS) berbasis web yang mengintegrasikan pengelolaan ZISWAF, qurban, inventaris barang, informasi kegiatan, serta pembayaran digital melalui QRIS. Dengan menerapkan metode Rapid Application Development (RAD), sistem ini dirancang agar dapat dikembangkan secara cepat dan sesuai dengan kebutuhan pengguna. Evaluasi dilakukan menggunakan pendekatan Customer Satisfaction Index (CSI), yang melibatkan 60 responden dari kalangan pengurus dan jamaah masjid. Hasil evaluasi menunjukkan bahwa seluruh layanan SIMMAS memperoleh nilai CSI di atas 85%, mencerminkan tingkat kepuasan yang tinggi, khususnya pada fitur jadwal kajian. Meski demikian, masih terdapat ruang untuk perbaikan, terutama pada aspek responsivitas dan empati dalam layanan keuangan dan pengelolaan inventaris. Penelitian ini diharapkan dapat menjadi dasar pengembangan berkelanjutan SIMMAS dalam mendukung tata kelola masjid yang lebih efektif, efisien, dan berbasis digital. Kata Kunci: kepuasan pengguna; sistem informasi masjid; CSI; SIMMAS; ZISWAF